Real-time TEM observations of ice formation in graphene liquid cell. Issue 15 (22nd March 2023) - Phakatkar, Abhijit H.; Megaridis, Constantine M.; Shokuhfar, Tolou; Shahbazian-Yassar, Reza
Abstract : Study of nucleation and growth dynamic events of cubic-phase ice crystals at TiO2 –water nanointerface. Abstract : The study of ice nucleation and growth at the nanoscale is of utmost importance in geological and atmospheric sciences. However, existing transmission electron microscopy (TEM) approaches have been unsuccessful in imaging ice formation directly. Herein, we demonstrate how radical scavengers – such as TiO2 – encased with water in graphene liquid cells (GLCs) facilitate the observation of ice nucleation phenomena at low temperatures. Atomic-resolution imaging reveals the nucleation and growth of cubic ice-phase crystals at close proximity to TiO2 –water nanointerfaces at low temperatures. Interestingly, both heterogeneously and homogeneously nucleated ice crystals exhibited this cubic phase. Ice crystal nuclei were observed to be more stable at the TiO2 –water nanointerface, as compared with crystals in the bulk liquid (homogeneous nucleation), suggesting the radical scavenging efficacy of TiO2 nanoparticles mitigating the electron beam by-products. The present work demonstrates that the use of radical scavengers in GLC TEM shows great promise towards unveiling the nanoscale pathways for ice nucleation and growth dynamic events.